Tinjauan yuridis pelaksanaan hak cipta dalam open access informasi - Sri Rumani (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2017)
Copyright is an exclusive right (morally and economically) automatically owned by the creator, as a treasure of the minds of science, art, and literature. The development of science and technology affects the protection and legal certainty for the creator. This means that the creators and creators have competence, considering Indonesia has ratified the world copyright agreement with the Presidential Decree No.19 of 1997. Consequently there is an obligation to enact Law No.28 of 2014. In Indonesia, copyright issues originally arranged in Auteursweet 1912 (Undang invited the rights of authors 1912), called